Phylogeny and taxonomy of Nigroporus (Polyporales, Basidiomycota) with four new species from Asia and Oceania - Xiang-Lin Li; Yu-Cheng Dai; Zhan-Bo Liu; Yu-Han Jiang; Hong-Gao Liu; Yuan Yuan (MycoKeys)
Nigroporus vinosus (Berk.) Murrill, first described from North America, was considered to be a common species in China. The existence of a species complex is confirmed through a phylogenetic analysis of samples examined. Based on morphological examination and molecular evidence, four new species are described as Nigroporus australianus, N. austroasianus, N. subvinosus and N. yunnanensis. They are characterized by pileate, effused-reflexed to resupinate, purplish, vinaceous to brown basidiomata when fresh, mostly becoming brown when dry. Nigroporus australianus is characterized by narrower basidiospores measuring 3.4–4.1 × 1.3–1.5 µm, thicker contextual hyphae measuring 3.2–6.4 µm in diam and a geographical distribution in Australia. Nigroporus austroasianus is characterized by smaller pores measuring 10–13 per mm, generative hyphae dominant in the tube trama, small basidiospores measuring 3–4.1 × 1.5–2 μm and a distribution in Malaysia and tropical to subtropical regions of China. Nigroporus subvinosus is characterized by skeletal hyphae with thin to slightly thick walls, barrel- to pear-shaped basidia, and long cystidioles measuring 10–18 µm and is common in Asia. Nigroporus yunnanensis is characterized by thinner pilei measuring 2.5 mm thick at the base, bigger basidiospores measuring 4–4.5 × 1.9–2.2 μm and is found only in Yunnan. The 2-gene (ITS+nLSU) analysis of the Steccherinaceae indicated that the four new species nested in the Nigroporus clade. The 3-gene (ITS+nLSU+TEF1) analysis of the genus Nigroporus showed that N. australianus formed a monophyletic lineage, N. subvinosus was sister to N. austroasianus and N. yunnanensis, and N. austroasianus was sister to N. yunnanensis. Furthermore, N. vinosus sensu stricto is also distributed in Asia.